Architecture as a celebration of multi-culturalism: revisiting Fatehpur Sikri - Mahmod, Shaukat; Denan, Zuraini; Jahn Kassim, Puteri Shireen (IIUM Press, 2014)
Fatehpur Sikri, Agra, India, a UNESCO World Heritage site, has been the subject of various scholarly articles and books in the past. This book represents a revisit to this famous complex as a constant reminder of a multi-cultural and multi-faith stance of the Mughal civilisation in general, and a hallmark of Akhbar’s reign and philosophy of leadership in particular. One is constantly reminded of the possibilities of human and cultural co-existence – unity within multiplicity-where traditions from different religious, world views and backgrounds come together. It is this distinctive balance and equipoise between different worlds and cultures that embodies Fatehpur Sikri. This ethos is reflected in the many aspect of the architecture of this complex – from its unique and innovative style from diverse religious and cultures- to its ingenious planning, layout and exquisite architectural details. There is a powerful synthesis of various regional schools of architectural craftsmanship such as Gujarat and Bengal, Hindu and Jain architecture and traditional Islamic elements. According to contemporary historians, seeking to have the best of worlds, including to retain the memory of his past heritage and yet to celebrate the present, Akhbar sought and managed to combine strands from his ancestor’s Persian style with the influence of Indian traditions which is celebrated amongst others in the typically Indian ornamentation based on the pattern and forms derived from Arab-Islamic and central Asian traditions. In its entirety, the monuments at Fatehpur Sikri celebrate the notion of the co-existence of man-kind and cultures. The assimilation of diverse regional architectural influences and the all-embracing ethos of the Mughal civilisation of its time is brought to light in an analysis of this complex. This book provides a refreshing historical account of the trajectory of events that brought to the creation of the complex, followed by a narrative of its architecture, planning and ornamentation. Fatehpur Sikri remains a testament of humanities’ shared values and the potentialities of cultural richness, and co-existence. Its architecture serves as a reminder to humanity to pursue such values, idealism and vision in multicultural world.